1986
DOI: 10.1111/j.1467-8624.1986.tb00263.x
|View full text |Cite
|
Sign up to set email alerts
|

Television Viewing at Home: Age Trends in Visual Attention and Time with TV

Abstract: The TV-viewing behavior of 99 families with young children was videotaped by automated time-lapse recording equipment placed in homes for 10-day periods. The 99 families comprised 460 individuals from infants to 62 years of age. Time-sample analyses of 4,672 hours of recordings indicated that the TV-viewing room contained no viewers 14.7% of the time that the TV was on. There were no age trends in time spent with television. Percent visual attention to television increased greatly across the preschool years, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
1

Year Published

1988
1988
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 15 publications
0
31
0
1
Order By: Relevance
“…4 The finding that screen time increased with age in this age range is also consistent with studies from Australia 5 and the US, 3,24,35 which show that screen time peaks at age 12-13 years -an age where the comprehensibility of TV shows plateaus. 36 In this study, SES emerged as a moderate correlate of screen time. There have been consistent reports of higher television viewing in low SES groups in adults.…”
Section: Minutes)mentioning
confidence: 60%
“…4 The finding that screen time increased with age in this age range is also consistent with studies from Australia 5 and the US, 3,24,35 which show that screen time peaks at age 12-13 years -an age where the comprehensibility of TV shows plateaus. 36 In this study, SES emerged as a moderate correlate of screen time. There have been consistent reports of higher television viewing in low SES groups in adults.…”
Section: Minutes)mentioning
confidence: 60%
“…These findings are particularly relevant given a recent increase in commercially available infant-directed programming and a subsequent increase in television exposure during infancy. During the 1970s children were first exposed to television on a regular basis at approximately 2.5 years (Anderson, Field, Collins, Lorch, & Nathan, 1985;Anderson & Levin, 1976;Anderson, Lorch, Collins, Field, & Nathan, 1986). Since then, however the media landscape has changed.…”
Section: Discussionmentioning
confidence: 99%
“…Although little work has been done concerning the amount of TV viewing by children under 2 years of age, one study found that they were exposed to an average of about 2 hours of television a day (Hollenbeck, 1978; see also Anderson, Lorch, Field, Collins, & Nathan, 1986). Systematic home observations of infants reveal that TV viewing is interspersed throughout the infant's day, including during eating, diaper changing, and other ordinary routines (Lemish & Rice, 1986).…”
mentioning
confidence: 99%